Survey of Mycotoxins in Corn Distillers’ Dried Grains with Solubles from Seventy-Eight Ethanol Plants in Twelve States in the U.S. in 2011 - Khatibi, Piyum A. (MDPI, 2014)
Fuel ethanol co-products known as distillers’ dried grains with solubles (DDGS) are a significant source of energy, protein, and phosphorous in animal feed. Fuel ethanol production may concentrate mycotoxins present in corn into DDGS. One hundred and forty one corn DDGS lots collected in 2011 from 78 ethanol plants located in 12 states were screened for the mycotoxins deoxynivalenol (DON), 15-acetyldeoxynivalenol (15-ADON), 3-acetyldeoxynivalenol (3-ADON), nivalenol (NIV), and zearalenone (ZON). DON ranged from <0.50 to 14.62 μg g(−1), 15-ADON ranged from <0.10 to 7.55 μg g(−1), and ZON ranged from <0.10 to 2.12 μg g(−1). None of the DDGS lots contained 3-ADON or NIV. Plants in OH had the highest levels of DON overall (mean of 9.51 μg g(−1)), and plants in NY, MI, IN, NE, and WI had mean DON levels >1 and <4 μg g(−1). Twenty six percent (36/141) of the DDGS lots contained 1.0 to 5.0 μg g(−1) DON, 2% (3/141) contained >5.0 and <10.0 μg g(−1) DON, and 3% (4/141) contained >10.0 μg g(−1) DON. All DDGS lots contaminated with unacceptable levels of DON evaded detection prior to their commercial distribution and were likely sold as feed products.